130 PROGNOSTIC IMPLICATION OF NEUTROPHIL-LYMPHOCYTE RATIO (NLR) IN MYOCARDITIS: RESULTS FROM A MULTICENTRE, MULTINATIONAL STUDY. (15th December 2022) - Baggio, Chiara; Cannatà, Antonio; Scott, Paul; Bromage, Daniel; Piper, Susan; Mcdonagh, Theresa; Merlo, Marco; Sinagra, Gianfranco
Abstract: Background: Neutrophil–lymphocyte ratio (NLR) is an easily obtained inflammatory biomarker. Recently it has emerged as baseline NLR is independently associated with incident cardiovascular (CV) events and all-cause mortality. However, its role in acute myocarditis (AM) has not been evaluated. Purpose: The aim of the present study was to investigate the prognostic value of NLR in patients with AM. Methods: All consecutive patients with a diagnosis of AM admitted to two tertiary referral cardiac centres (King's College Hospital, London, UK and Azienda Sanitaria Universitaria Giuliano-Isontina, Trieste, Italy) between October 2006 and June 2020 were included in the study. Diagnosis was confirmed by either cardiac magnetic resonance or endomyocardial biopsy. The outcome measure was all-cause mortality. Patients were divided into two groups according to NLR value defined in previous studies (i.e, 2.5). Results: A total of 260 patients with AM were included in the study. Baseline characteristics were comparable in both groups. Approximately two thirds of patients were males (n=175, 67%) with a mean age of 45±16 years. Main clinical presentation was predominantly infarct-like (n=189, 73%), followed by heart failure (HF) (n=46, 18%) and arrhythmic (n=25, 10%). Patients admitted with a HF presentation were more prevalent in the group with elevated NLR, while no difference was found in the other clinical presentations. For all patients, ECG features were comparable between groups. However, patients with elevated NLR presented with slightly lower LVEF (54±11% vs 49±13% respectively, p=0.001). Higher NLR was associated with worse prognosis (Figure 1, p=0.02). Conclusions: The NLR is a promising and accessible inflammatory biomarker. In patients with AM, elevated NLR is associated with worse prognosis. Further research is advocated to confirm these data in larger populations. Figure 1. Kaplan-Meier curves for all-cause mortality in patients with AM according to NLR.